„Tabula Rasa”. O medium i pamięci w odniesieniu do twórczości Sarah Charlesworth i pism Rosalind E. Krauss - Filip Pręgowski (Quart)
The article examines a series of serigraphs by American artist Sarah Charlesworth, titled Tabula Rasa, created in 1981, and analyses them in the context of the artistic medium. The serigraphs by Charlesworth, who is associated with the Pictures Generation movement, challenge the semiotic interpretation of images as carriers of ideological messages or allegorical structures, a perspective commonly held by critics from the Pictures circle. Earlier works by the artist, referenced in the article, can also be read through this lens. Due to its reinterpretation of Joseph Nicéphore Niépce’s 1832 or 1833 photograph of a set table, which is shrouded in uncertainty and ambiguity, Tabula Rasa prompts a reconsideration of the artistic medium and its contested status in the context of the so-called post-medium era. The primary point of reference for these considerations are the writings of American “October” journal critic Rosalind E. Krauss, particularly her book Under Blue Cup (2011).